REFORMATIVE PECULIARITIES OF THE NATIONAL AND INTERNATIONAL ECONOMIES UNDER CONDITIONS OF DIGITALIZATION - O. Klochkova (Вестник Северо-Кавказского федерального университета, 2022)
The article examines the role of digitalization of the economy at the national and international levels, namely, the impact of digitalization on the transformation of national and international economies in the context of improving their efficiency and competitiveness. The essence of the digital economy was studied, as well as the features of its formation at the current stage of development of world economic relations. The relevance of the system implementation of digital technologies in the Russian Federation was evaluated. The article analyzes current trends in the formation of the digital economy in countries with a high level of technological development. Challenges on the way to active digitalization were identified. If they are successfully overcome, society and the state will be able to implement the digital economy in life.